2021
DOI: 10.17309/tmfv.2021.3.12
|View full text |Cite
|
Sign up to set email alerts
|

The Relations of Using Digital Media and Physical Activity with the Physical Fitness of 4th and 5th Grade Primary School Students

Abstract: The study purpose was to determine the relations of using digital media and physical activity with the physical fitness of 4th and 5th grade students of the state of Ngablak Elementary School in the academic year 2019/2020, Turi, Sleman Regency both individually and wholly. Materials and methods. This research is a correlative study, which aims to find out whether there is a relationship between independent variables and dependent variables. The population of this study was 49 students from 4th and 5th g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…The study found that the peculiarity of learning is the speed of mastering the exercises of different series of training tasks, as well as the influence of the mode of physical exercises on motor skills development in boys aged 14 and 15. The obtained data supplement the information about motor skills development in schoolchildren (Samsudin, Setiawan, Taufik, & Solahuddin, 2021;Listyarini, Alim, Oktaviani, Putro, Kristiyanto, Margono, & Pratama, 2021;Abhaydev, Bhukar, & Thapa, 2020), about the influence of exercise modes on the effectiveness of teaching (Ivashchenko, 2020;Kapkan, Khudolii, & Bartik, 2019;Marchenko, Jagiello, Iermakov, Ivashchenko, & Khudolii, 2021).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The study found that the peculiarity of learning is the speed of mastering the exercises of different series of training tasks, as well as the influence of the mode of physical exercises on motor skills development in boys aged 14 and 15. The obtained data supplement the information about motor skills development in schoolchildren (Samsudin, Setiawan, Taufik, & Solahuddin, 2021;Listyarini, Alim, Oktaviani, Putro, Kristiyanto, Margono, & Pratama, 2021;Abhaydev, Bhukar, & Thapa, 2020), about the influence of exercise modes on the effectiveness of teaching (Ivashchenko, 2020;Kapkan, Khudolii, & Bartik, 2019;Marchenko, Jagiello, Iermakov, Ivashchenko, & Khudolii, 2021).…”
Section: Discussionmentioning
confidence: 53%
“…In the context of developing fundamental movement skills, the process of teaching physical exercises at school is a priority task. The studies by Samsudin, Setiawan, Taufik, and Solahuddin (2021); Listyarini, Alim, Oktaviani, Putro, Kristiyanto, Margono, and Pratama (2021); Abhaydev, Bhukar, and Thapa (2020) focus on the patterns of motor skills development. Research revealed the influence of exercise modes and rest intervals on the effectiveness of teaching (Ivashchenko, 2020;Kapkan, Khudolii, & Bartik, 2019;Marchenko, Jagiello, Iermakov, Ivashchenko, & Khudolii, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…У процесі аналізу результатів навчання для виявлення закономірностей формування рухових навичок застовуються регресійний (Khudolii, 2019;Khudolii, Iermakov, & Bartik, 2020;Listyarini, Alim, Oktaviani, Putro, Kristiyanto, Margono, & Pratama, 2021), факторний (Ivashchenko, Berezhna, & Cieślicka, 2020;Ivashchenko, & Sirichenko, 2020) та дискримінантний аналіз (Broadhead & Church, 1982;Brusseau & Burns, 2018;Kermarrec & Michot, 2007).…”
Section: вступunclassified
“…This was clearly seen when researchers observed badminton athletes based on the needs analysis with the test of badminton athletes aged 17-18 years still not entering the criteria, namely the acquisition of a VO 2 max value of 40.80-47.80ml/minute/ body weight for male badminton athletes (Saifu et al, 2021). Consecutive smashes cause excessive fatigue, which affects technique and concentration (Listyarini et al, 2021). Experts agree that endurance plays a significant role in winning matches (Ramírez-delaCruz, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%